The Effect of Cooking Process and Shelf Life Evaluation of Retort Pouch Packed a Tradition Meat Curry “Kaoyuk” - Nakban, Supawadee; Nuwongsri, Sawitree; Sapbua, Dudsadee; Thorarit, Thippika (Journal of Food Health and Bioenvironmental Science, 2023)
Kaoyuk is a traditional meat curry of Trang province, Thailand. It is prepared as a standard recipe. A retort pouch is used because it is a convenient thermal process in which the texture and flavor should be maintained in something close to the original condition. The purpose of the research is to were investigate the effect of the pre-cooking time of Kaoyuk and the change in quality of retorted Kaoyuk after 12 months storage. The effect of the pre-cooking time of meat at 0, 60 and 120 min before retorted process were studied and the texture analyzed and a sensory evaluation undertaken. The result found that the pre-cooking time at 60 min provided the tenderest meat, the retorted Kaoyuk was softened and also more retained the sensory qualities of the original. The 60 min of pre-cooked Kaoyuk were packed in retort pouch with thermal process on F0=11 min (118°C) and stored at room temperature (25±5°C) for 12 months. Physical properties, chemical properties, microbial properties and sensory evaluation were conducted every 3 months. Meanwhile, there was a significant decrease of pH from 5.9 to 5.46 and cutting force required was also was decreased from 8116 g force to 6320 g force whereas color L* a* b* values increased. The Free Fatty Acid value (FFA) was increased from 0.54 to 0.97 % of oleic acid and Thiobarbituric acid values (TBA) was increased from 0.64 to 1.07 mg of MDA/kg meat but no significant (P>0.05) growth of microbial and the sensory evaluation conducted from 10 trained panelists were accepted. The result showed that the retorted Kaoyuk can be store at room temperature for 12 months whilst maintaining acceptable safety and customer satisfaction levels.